Forensic Investigation and Comparison of Blood Sample Referring to Thalassemia (Indian Journal of Forensic Medicine & Toxicology, 2020)
Identification of an individual is one of the significant features of forensic investigation. The present studywas conducted to study the difference between normal and thalassemic blood. The study was conductedon 40 blood samples aim to compare control and disease wet blood samples by using different methods ofmicroscopy. The comparison was done based on the morphology of the RBCs and red blood cell count. A(monolayer) thin blood film is prepared on a slide with a wet blood sample and observed under a compoundmicroscope. Red blood cell count is performed with the help of Neubauer’s chamber. Observation showsthe changes in the morphology of red blood cells in the thalassemic population as compared to the controlpopulation, moreover based on total RBCs count the number red blood cell count found higher in thethalassemic population as compared to the control. Both morphology and Count significantly differed fromthe control population. Thus, the present method can be used in the daily routine at forensic science casework.